Managerial share ownership and operating performance: Do independent and executive directors have different incentives?. (February 2014) - Khan, Arifur; Mather, Paul; Balachandran, Balasingham
We investigate the relationship between managerial share ownership (MSO) and earnings as a measure of operating performance in Australia. To mitigate potential earnings management, we also use discretionary accrual adjusted earnings as an alternative measure of performance. We document a negative relation between MSO and performance followed by a positive relation. We suggest that these unique results are an artefact of certain Australian institutional features and imply that the ownership–performance relation is context-specific, with the wider corporate governance systems influencing the theorised incentive effects. We also posit that executive directors and independent directors have different ownership–performance incentives. Our results are consistent with this proposition and suggest that independent directors may be immune to the theorised incentive alignment or entrenchment effects associated with share ownership.